The Political Economy of Dominant Investors - Enrico C. Perotti; Ernst-Ludwig von Thadden (Tinbergen Institute, 2004)
We allow the preference of a political majority to determine boththe corporate governance structure and the division of profits betweenhuman and financial capital. In a democratic society where financialwealth is concentrated, a political majority may prefer to restraingovernance by dispersed equity investors even if this reduces profits.The reason is that labor claims are exposed to undiversifiable risk, sovoters with small financial stakes may prefer lender (or large share-holder) dominance, as they choose lower risk strategies. The modelmay explain the great reversal phenomenon in the first half of the20th century (Rajan and Zingales, 2003), when some financially verydeveloped countries moved towards bank or state control as a finan-cially weakened middle class became concerned about income risk.We offer evidence using post WW1 inflationary shocks as the sourceof identifying exogenous variation.
Keywords: G28; G31; G32; G34; 330; government policy and regulation; capital budgeting; investment policy; financing policy; capital and ownership structure; mergers; acquisitions; restructuring; corporate governance; Corporate Governance; Finanzintermediation; Bank; Medianwähler-Modell; Ökonomische Theorie der Demokratie